Pharmacological inhibition of 17β-hydroxysteroid dehydrogenase impairs human endometrial cancer growth in an orthotopic xenograft mouse model - Xanthoulea Sofia; Konings Gonda F. J.; Saarinen Niina; Delvoux Bert; Kooreman Loes F. S.; Koskimies Pasi; Häkkinen Merja R.; Auriola Seppo; D’Avanzo Elisabetta; Walid Youssef; Verhaegen Frank; Lieuwes Natasja G.; et al. (Elsevier Ireland Ltd, 2022)
Endometrial cancer (EC) is the most common gynaecological tumor in developed countries and its incidence is increasing. Approximately 80% of newly diagnosed EC cases are estrogen-dependent. Type 1 17β-hydroxysteroid dehydrogenase (17β-HSD-1) is the enzyme that catalyzes the final step in estrogen biosynthesis by reducing the weak estrogen estrone (E1) to the potent estrogen 17β-estradiol (E2), and previous studies showed that this enzyme is implicated in the intratumoral E2 generation in EC. In the present study we employed a recently developed orthotopic and estrogen-dependent xenograft mouse model of EC to show that pharmacological in-hibition of the 17β-HSD-1 enzyme inhibits disease development. Tumors were induced in one uterine horn of athymic nude mice by  intrauterine injection of  the  well-differentiated human endometrial adenocarcinoma Ishikawa cell line, modified to express human 17β-HSD-1 in levels comparable to EC, and the luciferase and green fluorescent protein reporter genes. Controlled estrogen exposure in ovariectomized mice was achieved using subcutaneous MedRod implants that released either the low active estrone (E1) precursor or vehicle. A subgroup of E1 supplemented mice received daily oral gavage of FP4643, a well-characterized 17β-HSD-1 in-hibitor. Bioluminescence imaging (BLI) was used to measure tumor growth non-invasively. At sacrifice, mice receiving E1  and  treated with the  FP4643 inhibitor showed a  significant reduction in  tumor growth by approximately 65% compared to mice receiving E1. Tumors exhibited metastatic spread to the peritoneum, to the  lymphovascular space (LVI), and  to  the  thoracic cavity. Metastatic spread and  LVI  invasion were both significantly reduced in the inhibitor-treated group. Transcriptional profiling of tumors indicated that FP4643 treatment reduced the oncogenic potential at the mRNA level. In conclusion, we show that 17β-HSD-1 inhibition represents a promising novel endocrine treatment for EC.